Effectiveness of Two-Year versus One-Year Use of Dual Antiplatelet Therapy in Reducing the Risk of Very Late Stent Thrombosis after Drug-Eluting Stent Implantation - Poorhosseini, Hamid Reza (Tehran University of Medical Sciences, 2012)
BACKGROUND: Impact of 12 months’ versus 24 months’ use of dual antiplatelet therapy on the prevalence of stent thrombosis in patients undergoing percutaneous coronary intervention (PCI) with the drug-eluting stent (DES) is not clear. As a result, duration of dual antiplatelet therapy is still under debate among interventionists. METHODS: From March 2007 until August 2008, all consecutive patients with successful PCI who received at least one DES and were treated with dual antiplatelet therapy (Clopidogrel + Aspirin) were included. All the patients were followed up for more than 24 months (mean = 35.27 ± 6.91 months) and surveyed for very late stent thrombosis and major cardiovascular events. RESULTS: From 961 patients eligible for the study, 399 (42%) discontinued Clopidogrel after 12 months and 562 (58%) continued Clopidogrel for 24 months. The clinical and procedural variables were compared between the two groups. In the 12 months’ use group, two cases of definite thrombosis occurred at 18 and 13 months post PCI. In the 24 months’ use group, 2 cases of definite thrombosis occurred at 14 and 28 months post PCI, one of them with stenting in a bifurcation lesion. Five cases of probable stent thrombosis were detected at 21, 28, 32, 33, and 34 months after the procedure. It is of note that amongst the 10 cases of stent thrombosis, only 1(10%) thrombosis occurred when the patient was on Clopidogrel and Aspirin and all the other 9 (90%) cases of thrombosis appeared after the discontinuation of the dual antiplatelet therapy. CONCLUSION: Extended use of dual antiplatelet therapy (for more than 12 months) was not significantly more effective than Aspirin monotherapy in reducing the risk of myocardial infarction or stent thrombosis, death from cardiac cause, and stroke.